1988
DOI: 10.1093/oxfordjournals.aje.a114932
|View full text |Cite
|
Sign up to set email alerts
|

Acute Nonlymphocytic Leukemia and Residential Exposure to Power Frequency Magnetic Fields1

Abstract: Recent research has suggested that nonionizing radiation in the form of power-frequency magnetic fields may play some role in carcinogenesis in general and in acute nonlymphocytic leukemia in particular. Much of the epidemiologic evidence is preliminary in nature and the methods of previous studies have been criticized. In order to further evaluate this hypothesis, a population-based case-control study of adult acute nonlymphocytic leukemia and residential exposure to power-frequency magnetic fields was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
1
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 42 publications
2
70
1
1
Order By: Relevance
“…Savitz et al (1988) found that for leukaemia there was a stronger association with wire codes than with direct contemporary measures of field intensity. Severson et al (1988), however, found no association between either wire codes or direct measures of field intensity and the risk of acute nonlymphocytic leukaemia in adults.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Savitz et al (1988) found that for leukaemia there was a stronger association with wire codes than with direct contemporary measures of field intensity. Severson et al (1988), however, found no association between either wire codes or direct measures of field intensity and the risk of acute nonlymphocytic leukaemia in adults.…”
Section: Methodsmentioning
confidence: 85%
“…The subjects' exposure to ELF fields was categorised indirectly in these studies by the type and proximity of electricity transmission and distribution equipment variously within 40-150m of the subject's home. In addition, ELF magnetic field intensities were measured directly at all addresses in one study (Tomenius, 1986), and at most addresses in the two recent studies (Severson et al, 1988;Savitz et al, 1988).A number of studies of men likely to be exposed occupationally to power frequency electromagnetic fields have also suggested a raised risk of leukaemia, especially acute myeloid leukaemia (see Aldrich & Easterly, 1987;Savitz & Calle, 1987;Coleman & Beral, 1988). Interpretation of the evidence is made difficult by the complexity and ubiquity of human exposure to man-made ELF fields in modern society, and by the difficulty of obtaining satisfactory retrospective measures of this exposure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure measurements from electromagnetic fields representing each occupational category differ markedly across workplaces and industries [2][3][4][5][6][7][8][9][10][11] . In these studies, measurements for a given occupation were generally made at one worksite.…”
mentioning
confidence: 99%